INFLUENCE OF A LUCUMA-BASED CARBOHYDRATE BEVERAGE ON ATHLETES - Rumyana Krasteva; Albena Durakova; Adelina Bogoeva; Kornelia Choroleeva (Scientific Publishing House. NSA Press, 2020)
This study focuses on a carbohydrate-containing beverage with water, 1.5% skim milk powder and lucuma fruit powder (Pouteria Lucuma). The aim is to analyze the influence of the beverage on the sports performance of young men with different levels of motor activity. The analysis of the results was based on the changes in some biometric parameters and the level of motor activity of 8 young men (experimental group; EG) consuming the beverage half an hour before fitness exercises - bodybuilding workouts - within a three-month period of time. The results obtained from the tests were compared to the results shown by the 13 men in the control group (CG) for the same period of time without consuming the beverage. On the basis of the profiles of the respondents from both groups (EG and CG), we analyzed the changes in body composition and motor activity at the beginning and at the end of the three month period. The results obtained from the comparative analysis revealed that both groups manifested positive changes concerning the level of motor activity as a result of the training program. These positive changes turned out to be more significant in the EG with respect to maximum oxygen intake and plank endurance. We also analyzed the modifications in the correlational dependencies as regards EG parameters, as a result of which we established more significant dependencies at the end of the test period. The results of the present study show that the consumption of the lucuma-based carbohydrate beverage by the experimental group has a positive effect on the analyzed parameters.